2012
DOI: 10.1111/j.2042-7158.2012.01537.x
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone pharmacokinetics in the mouse: implications for potential stroke therapy

Abstract: A bolus intraperitoneal loading dose of progesterone followed by continuous delivery via osmotic minipump is an effective way of delivering progesterone to the brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…The accumulation of PROG after its intraperitoneal administration is reported to be higher in the brain than in plasma [28]. Thus, high levels of PROG are quickly found in the brain after injection, allowing a rapid action of this steroid in the brain.…”
Section: Discussionmentioning
confidence: 98%
“…The accumulation of PROG after its intraperitoneal administration is reported to be higher in the brain than in plasma [28]. Thus, high levels of PROG are quickly found in the brain after injection, allowing a rapid action of this steroid in the brain.…”
Section: Discussionmentioning
confidence: 98%
“…While our estimates suggest that doses below 8 mg/kg/day may be more effective in humans, only an empirically-based dose optimization in a Phase IIB trial under defined conditions (vehicle, route, dose, and schedule) can determine what dose or doses are optimal (Fig. 1 2,6,7,17–19 ).…”
Section: Overview Of the Phase II Clinical And Preclinical Reportsmentioning
confidence: 88%
“…The dosing is comparable to the median serum level (335 ng/mL, 2 days after initial dose) used in the SyNAPSe clinical trial. 2 The trajectories for the preclinical dosing are representative of two studies: a pharmacokinetic report showing PROG concentration in mice treated with 8 mg/kg/d of PROG delivered by implanted osmotic minipumps (simulating continuous infusion) 17 and the strong inverse relationship observed between serum PROG levels and percent cerebral edema following TBI in rats. 7 There are numerous reports that a dose of 8 mg/kg/d is effective for restoring behavioral functions in rodent models of TBI and stroke.…”
Section: Overview Of the Phase II Clinical And Preclinical Reportsmentioning
confidence: 99%
“…Our previous pharmacokinetic study demonstrated that progesterone delivered via i.p. injection has a very short half-life in both plasma and brain [ 27 ] but high progesterone concentrations in the brain can be achieved via mini pump infusion. There have only a few studies, involving progesterone and experimental stroke, which have reported infusion delivery in rats [ 4 ] and mice [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the current study was to evaluate if progesterone would be effective in conferring neuroprotection after the onset of experimental stroke when administered via osmotic mini-pump in adult mice. In a prior study from our laboratory, the pharmacokinetics of progesterone in mice using this dosing method were investigated, and found it to be effective in delivering progesterone to the target area of the brain [ 27 ]. The delivery of progesterone via osmotic mini-pumps in an experimental stroke model, induced via middle cerebral artery occlusion (MCAO), has not been demonstrated previously; mini-pump delivery could offer a more suitable dosing method with the advantages of reducing peaks and troughs in drug levels, the stress associated with repeated injections, and diminishing levels of release over time as seen with pellet implants.…”
Section: Introductionmentioning
confidence: 99%